Tumor Immune Microenvironment Components and Checkpoint Molecules in Anaplastic Variant of Diffuse Large B-Cell Lymphoma - Xu, Tianqi; Chai, Jia; Wang, Kaijing; Jia, Qingge; Liu, Yixiong; Wang, Yingmei; Xu, Junpeng; Yu, Kangjie; Zhao, Danhui; Ma, Jing; Fan, Linni; Yan, Qingguo; et al. (Frontiers in Oncology, 2021)
Background: Anaplastic diffuse large B-cell lymphoma(A-DLBCL) is a rare morphological subtype characterized by the presence of polygonal, bizarre-shaped tumor cells. Our previous research found that A-DLBCL displays many genetic alterations and biological features that differ greatly from those of ordinary DLBCL. However, the status of TIME components and checkpoint molecules in A-DLBCL remains unclear. Methods: 30 A-DLBCL patients were enrolled to study tumor immune microenvironment components and checkpoint molecules and their associations with clinicopathological features and prognosis. Results: Patients with A-DLBCL presented higher expression of PD-L1 (40% vs 10%, P=0.004)than patients with ordinary DLBCL. FISH analysis showed that extracopies of PD-L1 were more frequent in A-DLBCL cases than in ordinary DLBCL cases(23.3% vs4.0%, P=0.001). The numbers of PD-1+ TILs and CD8+T cells were significantly lower in A-DLBCL versus ordinary DLBCL. In contrast, the numbers of GATA3+ Th2 cells, FOXP3+ Tregs and CD33+ MDSCs were significantly higher in A-DLBCL than in ordinary DLBCL. The associations between clinicopathological features and tumor immune microenvironment cell frequency were analyzed in A-DLBCL patients. Briefly, the number of PD-1+ TILs was lower and the number of CD33+ MDSCswas higher in patients with mutated TP53 compared to those with wild-type TP53. The number of FOXP3+ Tregs was much lower in patients with a noncomplete response(CR) to chemotherapy than in those with a complete response. The number of CD8+ T cells showed a decreasing trend in patients with high IPI scores and in those with concurrent MYC and BCL2 and/or BCL6 abnormalities. Univariate survival analysis showed that patients with PD-L1+, mPD-L1+(PD-L1+ nonmalignant stromal cells) or mPD-L1+ status had a significantly poorer OS than those with PD-L1- status. An increase in the number of CD3+ T cells, FOXP3+ Treg cells and T-bet+ Th1 cells was significantly associated with prolonged OS in patients with A-DLBCL. Conclusion: Our study suggests that A-DLBCL displays a distinct pattern of tumor immune microenvironment components and checkpoint molecules that distinguish it from ordinary DLBCL. The analysis of tumor immune microenvironment components and checkpoint molecules could help in predicting the prognosis of A-DLBCL patients and determining therapeutic strategies targeting the tumor immune microenvironment.